PROSES PEMBELAJARAN MATEMATIKA PADA ANAK BERKEBUTUHAN KHUSUS TUNANETRA KELAS VII DI SMPLB KEDUNGKANDANG MALANG - Novi Nurhayati (UPT Penerbitan Universitas Jember, 2022)
The purpose of this study was to determine the process of learning mathematics in children with special needs with visual impairment. This study uses a qualitative descriptive method with observations and interviews. Qualitative data analysis is directed to analyze the process of learning mathematics in children with special needs with visual impairment. The subject of this research is the seventh grade students of children with special needs who are blind. The results of the study indicate that in the learning process the teacher uses the preparation stages needed in learning, the implementation stage of the teacher provides material and guides students and the evaluation stage together summarizes and concludes from the learning material. Blind students have difficulty in learning mathematics, where teachers have to dictate to students in the learning process, but students have high curiosity and enthusiasm for the material being taught. Meanwhile, the limitations of manipulative learning media and school facilities are an inhibiting factor in the mathematics learning process for blind children. Keywords: Blind, Mathematics Learning Process, Special Needs Children